Analisis Persepsi Pelanggan Terhadap Harga Sewa, Kualitas, dan Kenyamanan Bermain di Chieng Leong Hua Futsal Singkawang - Theodorus Yanzens (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2023)
The background of this research is seen from the increasingly promising development of the futsal business from time to time, where people are increasingly fond of playing futsal and making futsal a universal sport. Increasing competition among futsal business players requires business players to be able to innovate, improve the quality of facilities and the comfort of the playing area. The research objectives were (1) to find out the customer's perception of the rental price at Chieng Leong Hua Futsal Singkawang; (2) knowing the customer's perception of the quality of the facilities provided by Chieng Leong Hua Futsal Singkawang. (3) knowing the customer's perception of the comfort of playing at Chieng Leong Hua Futsal Singkawang. This research answers the problems raised. Overall, customer response is at a good level. However, there are things that need to be improved, such as facilities that respondents feel need to be developed and improved in quality. Keywords: perception, price, quality, facilities, comfort, Singkawang